Acute Experimental Pain Responses in Methadone- and Buprenorphine/Naloxone-Maintained Patients Administered Additional Opioid or Gabapentin: A Double-Blind Crossover Pilot Study. Issue 6 (24th August 2019) - Murnion, Bridin Patricia; Rivas, Consuelo; Demirkol, Apo; Hayes, Vicky; Lintzeris, Nicholas; Nielsen, Suzanne
Abstract: Objective: The study objective was to identify the analgesic efficacy of three different pharmacological strategies in patients receiving methadone or buprenorphine as opioid agonist treatment (OAT). The three pharmacological approaches, a) increasing maintenance methadone/buprenorphine dose by 30%, b) adding oxycodone, or c) adding a single dose of gabapentin, were compared with a control condition of the participant's usual OAT dose. Design: A randomized, controlled, double-blinded, double-dummy, within-subject crossover study. Subjects: Nine participants on stable doses of methadone and eight participants on stable doses of buprenorphine were recruited. Setting: An outpatient opioid treatment clinic in inner city Sydney, Australia. Methods: The cold pressor tolerance test was used to examine experimental pain threshold and tolerance. Ratings of subjective drug effects and safety measures (physiological and cognitive) were assessed. Results: There was no difference in the primary outcome measures of pain thresholds or tolerance between the conditions examined. Interindividual variability was evident. Differences in some subjective measures were identified, including lower pain recall, lower "bad effects, " and higher global satisfaction in the additional methadone condition. In the buprenorphine arm, increased drug liking and "bad effects" were detected with oxycodone administration, while increased subjective intoxication was identified with gabapentin. Conclusions: There was no evidence of an objective improvement in analgesia with any condition compared with control. Further research is required to optimize pain management strategies in this population.